Antifungal Screening of Bridelia ferruginea Benth (Euphorbiaceae) Stem Bark Extract in Mouthwash Formulations - Aremu Olusola Isaac; Adewoyin Ayomide Barakat (Islamic Azad University, 2017)
The plant Bridelia ferruginea Benth (Euphorbiaceae) has been known for its use in the management of oral thrush ethnomedicinally in various parts of Africa, a practice which has been justified by results of certain scientific studies. The aim of this study was to develop an appropriate dosage formulation, a mouthwash and evaluate the antifungal potential of this dosage formulation against a major causative organism of oral thrush, Candida albicans. Extraction of the stem bark was carried out with boiled distilled water, the extract was formulated into mouthwashes at concentrations of 0.5, 1.0, 1.5, 2.0 and 2.5%w/v. All formulations contained viscosity imparting agent, a sweetener and a preservative. Physical characterisation, viscosity, pH and palatability of the mouthwash formulations were determined. Agar-well diffusion method was used to assess antifungal activity of the formulations against Candida albicans and Nystatin oral suspension was used as reference compound. The results showed that Bridelia ferruginea stem bark extract mouthwash solutions were brown in colour, had agreeable odour and sweet astringent taste. The pH for all concentrations was in the range 5.41-5.63. The viscosity at spindle no 2, 60rpm range between 0.226-0.238 Pa.S for all concentrations studied. The formulations had antifungal activity against Candida albicans. The highest concentration (2.5%w/v) gave mean zone of inhibition of 25.50±0.71mm that was comparable with Nystatin oral suspension 28.00±1.41mm, a reference compound. The foregoing suggests that with little modification in the formulation especially the adjustment of the pH, Bridellia ferruginea mouthwash solutions may be developed into commercially useful preparations.